(untitled) (Foro de Educacion, 2020)
In 1975, the United Nations, under the auspices of its Educational, Scientific and Cultural Organization (UNESCO) and Environment Program (UNEP), established the International Environmental Education Program (IEEP). For two decades, IEEP aimed to accomplish goals ascribed to it by UNESCO member states and fostered communication across the international community through Connect, the UNESCO-UNEP environmental education newsletter. After reviewing UNESCO’s early involvement with the environment, this study examines IEEP’s development, beginning with its conceptual grounding in the 1968 UNESCO Biosphere Conference. It examines the 1972 United Nations Conference on the Human Environment held in Stockholm, moves on to the UNESCO-UNEP 1975 Belgrade Workshop, and continues with the world’s first intergovernmental conference dedicated to environmental education held in Tbilisi in 1977. The paper then uses Connect to trace changes in the form and content of environmental education. Across two decades, environmental education shifted from providing instruction about nature protection and natural resource conservation to fostering an environmental ethic through a problems-based, interdisciplinary study of the ecology of the total environment to adopting the concept of sustainable development. IEEP ultimately met with mixed success. Yet it was the primary United Nations program assigned the task of creating and implementing environmental education globally and thus offers a particularly useful lens through which to analyze changes in the international community’s understanding of the concept of the environment over time.